How Mass Layoffs Are Related to Lower Job Performance and Ocb Among Surviving Employees in Chile: An Investigation of the Essential Role of Psychological Contract - Lopez-Bohle, S (Routledge, 2017)
This study aimed to investigate how mass layoffs impact surviving employees in organizations. More specifically, this study ascertained the relationships between mass layoffs and employee work behaviors. It was theorized that mass layoffs will be negatively related to employee performance and organizational citizenship behaviors (OCB) through its relationships with job insecurity and psychological contract breach. Moreover, it was expected that perceived manager support would buffer against the negative relations of contract breach with employee performance and OCB. A study among 615 employees in multiple Chilean organizations showed support for the hypotheses: job insecurity and psychological contract breach mediated the relationships between mass layoffs and employee performance and OCB. We also found moderating relationships of manager support, but the relations of breach with performance and OCB were particularly negative when manager support was high, indicating feelings of betrayal among high-support employees in response to contract breach. Moreover, the relation of contract breach with performance was positive for low-support employees, and non-significant for high-support employees. Our study advances understanding of the processes underlying how mass layoffs influence employee behavior in the workplace, through introducing the psychological contract as a way of understanding the relationships. © 2016 Informa UK Limited, trading as Taylor & Francis Group.